Analysis of Outpatient Satisfaction at Health Service Facilities in Batam City - Restu Prihandini Widiar (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Nowadays, the level of competition between health service providers is increasingly high. Compared to inpatient care, outpatient services are developing more rapidly. One effort to win the competition is to improve the quality of health services and provide services according to patient needs so that it will provide patient satisfaction. In this study, patient satisfaction was identified based on 5 determinants of service quality, namely Reliability, Responsiveness, Assurance, Empathy and Tangibility. The aim of this research is to determine patient satisfaction based on determinants of service quality. The research was carried out using a survey method of filling out online questionnaires by respondents. The sampling technique used was Malhotra's theory with a sample size of 160 people. The research results show that the Customers Satisfaction Index (CSI) value for outpatients at health service facilities in Batam City is 79.6%, including in the satisfied category. All gap values ​​show negative results, the highest gap value is - 0.84 for the attribute of readiness to respond to patient requests and staff who are always polite. Meanwhile, the lowest gap value is -0.04 for the facility/service place attribute that looks attractive to look at. Therefore, it is necessary to gradually improve the quality of service in order to increase patient satisfaction which can be implemented based on service improvement priorities starting from the attribute that has the highest negative gap value. Keywords: patient satisfaction, outpatient, health service facilities.